Varieties of recollective experience. (3rd February 2020) - Kihlstrom, John F.
Abstract: Four variants on Tulving's "Remember/Know" paradigm supported a tripartite classification of recollective experience in recognition memory into Remembering (as in conscious recollection of a past episode), Knowing (similar to retrieval from semantic memory), and Feeling (a priming-based judgment of familiarity). Recognition-by-knowing and recognition-by-feeling are differentiated by level of processing at the time of encoding (Experiments 1–3), shifts in the criterion for item recognition (Experiment 2), response latencies (Experiments 1–3), and changes in the response window (Experiment 3). False recognition is often accompanied by "feeling", but rarely by "knowing"; d' is higher for knowing than for feeling (Experiments 1–4). Recognition-by-knowing increases with additional study trials, while recognition-by-feeling falls to zero (Experiment 4). In these ways, recognition-by-knowing is distinguished from recognition-by-feeling in much the same way as, in the traditional Remember/Know paradigm, recognition-by-remembering can be distinguished from recognition-without-remembering. Implications are discussed for dual-process theories of memory, and the search for the neural substrates of memory retrieval. Highlights: Tulving, 1985 distinction between "remembering" and "knowing" was a milestone in the study of memory and consciousness. Most computational and neuroscientific models of recognition construe "knowing" as a priming-based feeling of familiarity. "Knowing" can be dissociated from both conscious recollection and the feeling of familiarity. Remembering, knowing, and feeling differ in terms of the information about an event accessible at the time of retrieval.